Intergenerational variation in sexual health attitudes and beliefs among Sudanese refugee communities in Australia. Issue 1 (2nd January 2017) - Dean, Judith; Mitchell, Marion; Stewart, Donald; Debattista, Joseph
Abstract: The aim of this study was to develop intergenerational understanding of the factors perceived to be influencing the sexual health and wellbeing of young Sudanese refugees in Queensland, Australia. Data from 11 semi-structured, face-to-face interviews exploring sexual health knowledge, attitudes and behaviours with young people aged 16 to 24 years, and five focus groups with adults from the broader Queensland Sudanese community, were compared and contrasted. Findings indicate that sexual health-related knowledge, attitudes and beliefs, along with patterns of sexual behaviour, are changing post-resettlement and this creates considerable intergenerational discord and family conflict. Study findings provide an understanding of how the interplay between traditional cultural gender, parenting and relationship norms and perceived normative Australian beliefs and patterns of behaviour influence the construction of both young people's and their parents' attitudes to sexual health post-arrival. We suggest that sexuality education programmes adapted to the specific cultural- and age-related contexts need to be introduced early within the resettlement process for both young people and their families.